MANAGING MOBILITY FOR SUSTAINABLE TOURISM: EVIDENCE FROM INDONESIA - Bakty, Andi Fatimah Maoudy A; Jasman, Jasman (USN Kolaka, 2025)
Losari Beach, a prominent tourist destination in Makassar City, faces various challenges in mobility management during major events such as the Makassar International Eight Festival Forum (F8). The surge in tourist numbers often results in traffic congestion, increased carbon emissions, and pressure on public infrastructure. This study explores the application of sustainable transport concepts to address these issues, which have become a concern for both local communities and visiting tourists during large-scale events in Makassar. Through multimodal and intermodal approaches, transportation modes such as shuttle buses, cycling lanes, and pedicabs can be integrated to create environmentally friendly systems that enhance connectivity and improve the tourist experience.The revitalization of traditional transportation, such as equipping pedicabs with electric motors, is proposed as a short-distance transportation solution that not only supports carbon emission reduction but also reinforces the cultural heritage of Makassar. Additionally, transportation demand management (TDM) measures, such as high parking fees and incentives for using eco-friendly modes, can help reduce reliance on private vehicles in the Losari Beach area. This approach also encourages local community participation in sustainable transport systems through the training of pedicab drivers as tourist guides.The findings of this study indicate that sustainable transportation management in Losari Beach requires the integration of policies, infrastructure, and technology, as well as collaboration among governments, event organizers, and local communities. Implementing this concept not only reduces the negative environmental impacts of transportation but also aims to enhance the tourism appeal of Losari Beach by providing authentic cultural experiences. Consequently, this area can serve as a successful example of a sustainable tourism destination that empowers local communities